Diaspora Indonesia dan Usaha Mikro, Kecil, dan Menengah di Indonesia - Aknolt Kristian Pakpahan; Gracelia Yoshanty (Jurnal Ilmiah Hubungan Internasional, 2022)
The world is facing the biggest health crisis in the 21st century which is the COVID-19 pandemic. International trade activities are disrupted due to the total lockdown to stop the spread of this pandemic outbreak. International Monetary Fund (IMF), World Bank, and OECD showed the economic impact of the COVID-19 pandemic when economic growth will be decreased -4,9% to -6%. This also has an impact on the Indonesian economic sector which is dominated by the presence of Micro, Small and Medium Enterprises (MSMEs), namely the decline in export performance in line with the contraction of economic growth and purchasing power in various countries. Indonesia needs help not only from inside the country and from international cooperation with other countries, but the involvement of the entire community wherever they are is needed to jointly resolve this pandemic. Indonesian diaspora community that is scattered in various parts of the world can be one of the solutions. This research focuses on how does the Indonesian diaspora community that scattered across the United States and Germany help Indonesia’s MSMEs by taking advantage of foreign markets. Through collaboration between representatives of the Government of Indonesia offices in the United States and Germany with Indonesian diaspora groups, various assistances were found such as informing Indonesia's potential MSME products, bridging meetings with business actors abroad, and conducting promotional activities to increase the export potential of Indonesian MSME products.